Cyclosporine A protects podocytes by regulating WAVE1 phosphorylation - Li, Xuejuan (Nature Publishing Group, 2015)
Accumulating evidence suggests that podocytes are direct targets of many classic antiproteinuric drugs. The immunosuppressive drug cyclosporine A (CsA), which is a calcineurin inhibitor, is used to treat proteinuric kidney diseases. One novel mechanism by which CsA reduces proteinuria is by directly stabilizing the podocyte cytoskeleton. Previous studies showed that calcineurin can directly regulate WAVE1 within mouse striatal slices. In this study, WAVE1 was expressed in podocytes and was localized in the podocyte cell bodies and foot processes (FPs). WAVE1 expression increased in both in vivo and in vitro models of puromycin aminonucleoside (PAN)-induced podocyte injury. CsA restored WAVE1 expression and also partially rescued the disordered F-actin arrangement after PAN injury. Co-immunoprecipitation assays showed that calcineurin directly interacted with WAVE1 and regulated WAVE1 phosphorylation in podocytes. Synaptopodin is a well-characterized target of CsA. WAVE1 overexpression and synaptopodin knockdown experiments directly demonstrated that WAVE1 expression is not dependent on synaptopodin expression, and vice versa. Overexpression of WAVE1 using a WAVE1 plasmid disrupted F-actin structure and promoted podocyte migration compared with the empty vector group. Therefore, WAVE1 may be a novel molecular target for the maintenance of podocyte FPs and for antiproteinuric treatment in the future.